2012
DOI: 10.1088/0004-637x/753/1/36
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Wave Damping at Low Heights in a Polar Coronal Hole

Abstract: We have measured the widths of spectral lines from a polar coronal hole using the Extreme Ultraviolet Imaging Spectrometer onboard Hinode. Polar coronal holes are regions of open magnetic field and the source of the fast solar wind. We find that the line widths decrease at relatively low heights. Previous observations have attributed such decreases to systematic effects, but we find that such effects are too small to explain our results. We conclude that the line narrowing is real.The non-thermal line widths a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
102
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(120 citation statements)
references
References 55 publications
(89 reference statements)
16
102
2
Order By: Relevance
“…This is because our observations are mostly beyond peak EUV flux. Hahn et al (2012) have carefully examined the pervasive scattered light in a study of EIS spectra above the solar limb in their work on wave heating. The pervasive scattered light would tend to narrow our line profiles as the intensity of the real component decreases.…”
Section: Sources Of Errormentioning
confidence: 99%
See 1 more Smart Citation
“…This is because our observations are mostly beyond peak EUV flux. Hahn et al (2012) have carefully examined the pervasive scattered light in a study of EIS spectra above the solar limb in their work on wave heating. The pervasive scattered light would tend to narrow our line profiles as the intensity of the real component decreases.…”
Section: Sources Of Errormentioning
confidence: 99%
“…This is in the opposite direction of our results. Furthermore, Hahn et al (2012) found that a huge contribution of scattered light (greater than 45%) was necessary to begin influencing their results. Because of the Hahn et al (2012) results and the fact that scattered light produces an effect opposite to the effect we are claiming to have found, we feel that scattered light is unimportant for this work.…”
Section: Sources Of Errormentioning
confidence: 99%
“…We extracted line intensities by fitting Gaussian functions to the spectra (see, e.g., Hahn et al 2012). In addition to the lines given in Table 1, we also analyzed other prominent lines in the EIS spectrum, which we used for the temperature analysis.…”
Section: Observations and Resultsmentioning
confidence: 99%
“…These five pointings were summed by averaging the data radially to form a single composite pointing. The details of this averaging are described by Hahn et al (2012). Here, we have further binned the data vertically in 8 pixel bins to increase the signal to noise.…”
Section: Coronal Holesmentioning
confidence: 99%
See 1 more Smart Citation